Toward the elimination of NTDs: application of cost-effective and sensitive molecular environmental surveillance tools—a pilot study - Hodgson, Juliet; Twieku, Gideon; Quarcoo, Gerard; Armah, Emmanuel; Osei-Atweneboana, Mike Yaw; Armoo, Samuel (Frontiers in Parasitology, 2024)
Neglected tropical diseases (NTDs) affect over a billion people worldwide. The 2021–2030 NTD road map calls for innovative and highly efficient interventions to eliminate or significantly reduce the burden of NTDs. These include sensitive and cost-effective diagnostic techniques for disease surveillance. Environmental surveillance has been employed effectively in this regard to measure and track infectious diseases such as polio on a population-wide scale. In this study, environmental surveillance was used as a cost-effective tool for the detection of soil-transmitted helminths (STHs) in Accra, Ghana, in an area that is populated by urban vegetable farmers. The activities of urban farmers expose them to the risk of STH infection, as well as impact the transmission in urban areas since leafy vegetables could carry infective stages of STHs. A total of 32 wastewater samples were collected from eight points on the Nima Creek (the main source of irrigation for the farmers) over a 7-week period. Real-time PCR and melt peak analysis were used to screen four STHs (i.e., Ascaris lumbricoides, Necator americanus, Ancylostoma duodenale, and Trichuris trichiura). This study revealed that A. lumbricoides (17 out of 32 wastewater samples, 53.3%) was the most prevalent STH, followed by A. duodenale (31.2%), T. trichiura (21.9%), and N. americanus (12.5%). Environmental surveillance helps in the detection of the types of STH pathogens circulating within the community and in the design of mass drug administration (MDA) strategies. This surveillance technique can also provide preliminary information for environmental modifications to help reduce STH transmission in line with the One Health approach recommended in the 2021–2030 NTD road map.